A TRANSCENDENTAL PHENOMENOLOGICAL STUDY OF THE MOTIVATIONS DRIVING FILIPINO LIBRARIANS TO WORK ABROAD - Jolo Van Clyde S. Abatayo (Chelonian Research Foundation, 2024)
This transcendental phenomenological study explores the motivations driving Filipino librarians to pursue careers abroad. The research addresses a critical gap in existing literature by providing an in-depth examination of the personal and professional factors that influence these individuals' decisions to work internationally. Employing Moustakas' (1994) transcendental phenomenological approach, the study gathered data from Filipino librarians employed in various countries, including the United Arab Emirates, Saudi Arabia, Bahrain, and Hungary. Semi-structured interviews were conducted and analyzed using NVivo, focusing on key themes such as career stagnation, personal aspirations, professional opportunities, and cultural adaptation. The findings reveal that motivations are deeply rooted in a combination of personal ambitions, professional growth, and the pursuit of financial stability. Moreover, the research underscores the significance of cultural adaptability and continuous learning in achieving success in international librarianship. The study contributes to the understanding of how international experiences enhance librarians' competencies and suggest implications for policy and practice in supporting the professional integration of librarians in global contexts.